Impact of time-outs on efficiency of man-up in water polo: An analysis of the differences between the three levels of water polo players - Hraste, M.; Jelaska, I.; Clark, C. C. T. (SportMont, 2020)
In water polo, time-outs last one minute and only a team in possession of the ball can request one; although there are diverse opinions whether a time-out is advantageous for the team in possession. The aims of this study were, firstly, to identify and to explain the impact of time-out on the efficiency of man-up in water polo, and secondly, to identify and to explain the differences in the efficiency of man-up in water polo between three qualitative levels of players. The sample consisted of 132 matches of the Adriatic Water Polo League, who were observed for indicators of man-up efficiency. There was no statistically significant difference between man-up efficiency played after a time-out and man-up efficiency played without a time-out. Additionally, the Kruskal-Wallis test partially confirmed the existence of significant differences between three qualitative levels of water polo players. There is a reasonable possibility that the differences between levels are generated by the differences in tactical knowledge, motor ability, and scoring ability. Trainers can apply the results of this study for the selection of appropriate tactical solutions and the optimization of training processes among elite and sub-elite water polo players. Additionally, the study`s results can be the basis for further research dealing with exploring the dynamics of water polo, observed through recent changes in the rules.